An Open-label Randomized Controlled Trial to Compare Weight Gain of Very Low Birth Weight Babies with or without Addition of Coconut Oil to Breast Milk. (23rd March 2018) - Arun, Sumitha; Kumar, Manish; Paul, Thomas; Thomas, Nihal; Mathai, Sarah; Rebekah, Grace; Thomas, Niranjan
Abstract: Background: Nutritional guidelines involving the feeding of very low birth weight babies (VLBW) recommend addition of Human Milk Fortifiers to breast milk. Owing to financial constraints, it is a practice in low- and middle-income countries (LMIC) to add coconut oil to aid better weight gain. There are inadequate data on improvement of growth parameters with oral coconut oil supplementation of breast milk. Methods: In this randomized controlled trial, we measured growth parameters and body composition of 60 babies who received either breast milk with coconut oil or breast milk alone. Randomization was stratified according to intrauterine growth appropriate for gestational age ( n  = 30) and small for gestational age ( n  = 30). Results: There was no difference in weight gain between the two groups. The weight gain velocity was 15 ± 3.6 and 14.4 ± 3.4 g/kg/day ( p value = 0.49) in the breast milk alone and in the breast milk with coconut oil group, respectively. There was no difference in increase in head circumference and length. Triceps skinfold thickness ( n  = 56) was similar in both groups, but subscapular skinfold thickness was significantly more in the coconut oil group. Total body fat percentage did not differ between the groups (25.2 ± 4.3 vs. 25.5 ± 4.3%, p  = 0.79). Conclusion: Oral supplementation of coconut oil along with breast milk did not increase growth parameters or result in change in body composition in very low birth weight (VLBW) babies.